2011
DOI: 10.1111/j.1740-8709.2010.00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intakes of polyunsaturated fatty acids among pregnant Mexican women

Abstract: Nutritional demands for docosahexaenoic acid (DHA) are high during pregnancy. Diets low in DHA and long-chain polyunsaturated fatty-acids (LC-PUFA) in pregnancy are associated with poorer DHA status and slower reestablishment of maternal stores. To assess intakes of LC-PUFA among urban pregnant women in Central Mexico, we conducted a cross-sectional survey in Prenatal Clinic at the General Hospital No. 1 of the Mexican Society Security Institute, Cuernavaca, Morelos, Mexico. We ascertained intakes over past th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 25 publications
(40 reference statements)
1
38
1
1
Order By: Relevance
“…We assessed maternal dietary intake at 18-22 wk gestation using a 110-item FFQ that included specific questions about consumption of sources of DHA such as freshwater fish, seafood, canned tuna and sardines, salmon, trout, and cod liver oil in the previous 3 mo (24,25). Estimates of (n-3) PUFA intake ascertained using this FFQ correlated reasonably well with erythrocyte membrane (n-3) PUFA phospholipid concentration (26).…”
Section: Methodsmentioning
confidence: 98%
“…We assessed maternal dietary intake at 18-22 wk gestation using a 110-item FFQ that included specific questions about consumption of sources of DHA such as freshwater fish, seafood, canned tuna and sardines, salmon, trout, and cod liver oil in the previous 3 mo (24,25). Estimates of (n-3) PUFA intake ascertained using this FFQ correlated reasonably well with erythrocyte membrane (n-3) PUFA phospholipid concentration (26).…”
Section: Methodsmentioning
confidence: 98%
“…An inverse association between socioeconomic level and intake of alpha-linolenic acid was also detected in pregnant Mexican women with diets comprising a lipid profile close to that of the pregnant women from Botucatu. In Mexico, as in Brazil, access to food sources of omega-3 fatty acids appears linked to economic constraints [20], a factor to be considered when selecting foods to encourage intake of omega-3 fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…DHA intakes in our study population were low (median: 80 mg/day) compared with the recommended intake of at least 200 mg/ day. 26,40 Intake of n-3 PUFA in the United States is an estimated 1.6 g/day, and intake of DHA is ϳ100 to 200 mg/day. 41 Our study population experienced lower infectious disease rates than are reported from many developing countries, in particular for diarrhea and fever.…”
Section: Discussionmentioning
confidence: 99%